Control of translation during the unfolded protein response in maize seedlings: Life without PERKs. (30th July 2020) - Kanodia, Pulkit; Vijayapalani, Paramasivan; Srivastava, Renu; Bi, Ran; Liu, Peng; Miller, W. Allen; Howell, Stephen H.
Abstract: The accumulation of misfolded proteins in the endoplasmic reticulum (ER) defines a condition called ER stress that induces the unfolded protein response (UPR). The UPR in mammalian cells attenuates protein synthesis initiation, which prevents the piling up of misfolded proteins in the ER. Mammalian cells rely on Protein Kinase RNA‐Like Endoplasmic Reticulum Kinase (PERK) phosphorylation of eIF2α to arrest protein synthesis, however, plants do not have a PERK homolog, so the question is whether plants control translation in response to ER stress. We compared changes in RNA levels in the transcriptome to the RNA levels protected by ribosomes and found a decline in translation efficiency, including many UPR genes, in response to ER stress. The decline in translation efficiency is due to the fact that many mRNAs are not loaded onto polyribosomes (polysomes) in proportion to their increase in total RNA, instead some of the transcripts accumulate in stress granules (SGs). The RNAs that populate SGs are not derived from the disassembly of polysomes because protein synthesis remains steady during stress. Thus, the surge in transcription of UPR genes in response to ER stress is accompanied by the formation of SGs, and the sequestration of mRNAs in SGs may serve to temporarily relieve the translation load during ER stress.